Ph measurement of cement-based materials: The effect of particle size - Loh P.Y.; Shafigh P.; Katman H.Y.B.; Ibrahim Z.; Yousuf S. (MDPI, 2023)
Healthy reinforced concrete should be highly alkaline to safeguard the passive protective film for reinforcement of steel bars against corrosion. pH measurement is gaining importance in research of cement-based materials (CBMs), such as paste, mortar and concrete, as well as in structural health monitoring and forensic engineering applications. However, insufficient information is available regarding the most practical, economical and applicable quantitative pH measurement method for CBMs from the sampling to measurement stage. Existing recommended methods for measuring pH have many variables that need to be investigated to determine how they influence the pH value. Samples were recommended to be ground into very fine particles for pH measurement. Preparing very fine particles of CBMs is costly and time consuming, while larger particles, with sizes similar to sand particles, are easier to obtain, without needing special equipment. This study aims to investigate the effect of different particle sizes on the pH of cement mortar. Mortar specimens were crushed and sieved to obtain different ranges of particle sizes to measure the pH values. Results showed that specimens with large particle sizes (between 600 m and 4.75 mm) can produce similar results to specimens with very fine particle sizes (<600 m) by increasing the solid-to-solvent ratio or the leaching time. 2021 by the authors. Licensee MDPI, Basel, Switzerland.